How to perform surgical planning for hemodialysis access? Routine preoperative doppler ultrasound mapping - Doğan, Nurullah; Nas, Omer Fatih (The European Research Journal, 2021)
Objectives: The aim of the study was to evaluate the effect of routine preoperative Doppler ultrasound mapping on surgical planning in patients having hemodialysis fistulas. Methods: Patients with arteriovenous fistulas (AVF) or arteriovenous grafts (AVG) were retrospectively reviewed between June 2010 and July 2017. Physical findings, preoperative Doppler ultrasound and postoperative findings of 1924 patients were reviewed. Results: Fistula maturation rate was 82%. The average duration of patency of the first fistula was 19 months (3-38 months) and the duration for a previous fistula operation history was 11 months (1-14 months). Patency rate after 6 months was 78%. Mean maturation times for AVF and AVG were 70 and 28 days, respectively. Doppler ultrasound findings affected operation plans of surgeons in 227 of 908 (25%) first time fistula operation patients, and in 569 of 1016 (56%) patients with previous history of fistula surgery. Review of two groups revealed that Doppler ultrasound affected 41% (796/1924) of fistula planning of surgery for hemodialysis. Conclusions: We suggest that preoperative Doppler ultrasound should be routinely performed in patients undergoing fistulation for hemodialysis. Furthermore, a vascular radiologist and a vascular surgeon should decide the surgical plan together.